2018
DOI: 10.5194/acp-18-5799-2018
|View full text |Cite
|
Sign up to set email alerts
|

Organic aerosol in the summertime southeastern United States: components and their link to volatility distribution, oxidation state and hygroscopicity

Abstract: Abstract. The volatility distribution of the organic aerosol (OA) and its sources during the Southern Oxidant and Aerosol Study (SOAS; Centreville, Alabama) was constrained using measurements from an Aerodyne high-resolution time-of-flight aerosol mass spectrometer (HR-ToF-AMS) and a thermodenuder (TD). Positive matrix factorization (PMF) analysis was applied on both the ambient and thermodenuded high-resolution mass spectra, leading to four factors: more oxidized oxygenated OA (MO-OOA), less oxidized oxygenat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 74 publications
5
24
0
2
Order By: Relevance
“…SOA parameterizations in 3-D chemistry and climate models should be informed by these results and incorporate strategic simplifications that capture key changes in molecular-level composition. Existing bulk composition metrics include elemental ratios 26 , bulk carbon oxidation state 34 , mass spectra fragments (e.g., m/z 43/44) 40 , functional group fractions 41 , or often generic statistically-derived source apportionment factors (e.g., more oxidized oxygenated OA (MO-OOA), less oxidized oxygenated OA (LO-OOA)) 42 . Nontargeted molecular-level speciation should be used to elucidate variations between seemingly similar bulk metric values within data sets, between studies, and in model evaluations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SOA parameterizations in 3-D chemistry and climate models should be informed by these results and incorporate strategic simplifications that capture key changes in molecular-level composition. Existing bulk composition metrics include elemental ratios 26 , bulk carbon oxidation state 34 , mass spectra fragments (e.g., m/z 43/44) 40 , functional group fractions 41 , or often generic statistically-derived source apportionment factors (e.g., more oxidized oxygenated OA (MO-OOA), less oxidized oxygenated OA (LO-OOA)) 42 . Nontargeted molecular-level speciation should be used to elucidate variations between seemingly similar bulk metric values within data sets, between studies, and in model evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Future work should determine which chemical/physical properties are most prone to changes with compositional variability, and how observed compositional changes at different locations will affect SOA properties. For example, while there is some correlation between hygroscopicity and average O/C 42,46 , O/C distribution is also important in determining volatility 42,47 . Additionally, metrics like O/C, which do not reflect changes in the isomeric composition of a mixture, may be misleading in characterizing an aerosol mixture because overall O/C may remain fairly consistent with time, and therefore seemingly indicate consistent chemical composition.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kostenidou et al (2018) found that SOA species with higher MFR can be more volatile because of lower enthalpy of vaporization. As a result, a mass transfer model taking into account during the dynamic evaporation of the aerosol all these properties that affect volatility as vaporization enthalpy residence time, particle size and OA concentration into account is needed for better interpretation of OA volatility measurements (Riipinen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Volatility distribution ∆H am 1 0 -8 10 -7 10 -6 10 -5 10 -4 10 -3 10 -2 10 -1 10 0 10 1 10 2 , 2008, . (Lee et al, 2010.…”
Section: Speciesmentioning
confidence: 99%
“…g Sampling site is Centreville, and the sampling time is June/July 2013 (Kostenidou et al, 2018). This estimation use the transfer model of Riipinen et al (2010), and the uncertainties are calculated by Karnezi et al (2014).…”
mentioning
confidence: 99%